Taku Glacier borehole data, Alaska, 2014-2016 - Martin Truffer (Arctic Data Center, 2018)
This project investigated the feedbacks between glacial erosion and glacier dynamics at Taku Glacier, Alaska, which is currently in the advancing phase of the tidewater glacier cycle. We measured the spatial and temporal patterns of sediment erosion, properties of basal till, basal water pressure, basal motion, ice deformation, surface velocities, surface mass balance, and changes in surface elevation and terminus position. Data was collected from spring 2014 through fall 2016. The project consisted of time-lapse photography, borehole instrumentation, GPS surveys, active seismics, and basic meteorological measurements. All field work was conducted close to the glacier terminus. This data set was collected in a hot-water drilled borehole on Taku Glacier between August 2015 and August 2016. The data are from a newly developed 'drag spool', which consisted of a 48 cm long anchor that was hammered to at least 23 cm into subglacial till and a 1.5 m long section that was installed in the basal ice. The data set consists of the amount of line that was paid out as the two sections separated, the water pressure in the borehole, and three axis tilt for both the ice section and the sediment anchor.